Questions of culture in the life of offshored Chinese capital - Julia Chuang (economic sociology. perspectives and conversations, 2022)
Since 2008, private Chinese family wealth has been rapidly expatriated overseas. Chinese citizens are currently transferring money out of the country at a rate of around 450 billion USD per year (Fan 2016). One industry study estimates that 60 percent of Chinese citizens with a net worth of more than 1.5 million USD are either in the process of moving abroad or considering doing so (Hurun Report 2021).
Keywords: 300